Didactic-Methodological Innovations in Ruralnet's Virtual Context and Satisfaction of the University Students - Lourdes Villalustre Martínez; M. Esther del Moral Pérez (Universidad Autónoma de Madrid, 2016)
In the subject Education in the rural area (Ruralnet), -subject to the grade of Pedagogy of the University of Oviedo and offered the Virtual Shared Campus of the G9-, it developed different didactic - methodological innovations, during the period that includes the courses 2005-2006, 2006-2007 and 2007-2008, in relation so much: to the didactic adopted strategies; to the formulation of formative activities of individual character (studies of cases, conceptual maps, mental maps, and search of information across the Internet, etc.) and collaborative activity (Gameproyect) attending to the cognitive diversity of the students, and the use of the tools of the Web 2.0 (forums, wikis, blogs); as well as, to the virtual context and / or blended context in the one that developed the action tutorial. Also, we show the opinions of the students about the innovations implemented in the subject. The results show students' preferences as to the approach of collaborative activities that support the approach to similar situations that could develop as independent professionals, as well as individual practice approach based on the realization of concept maps, especially for students with active learning style and pragmatic. Demanding a quick tutorial and virtualized solve their cuestions and guide their learning.